Analysis of ASTEC-Na capabilities for simulating a loss of flow CABRI experiment. (August 2016) - Flores y Flores, A.; Matuzas, V.; Perez-Martin, S.; Bandini, G.; Ederli, S.; Ammirabile, L.; Pfrang, W.
Highlights: ASTEC-Na results for CABRI BI1 test have been compared with experimental data. The ASTEC-Na calculations reached the boiling onset within the error bar of the test. The coolant axial profile in ASTEC-Na fit almost perfectly with the experimental data. All the calculations have a good agreement with the two-phase front downwards. All the calculations have a worse agreement with the two-phase front upwards. Abstract: This paper presents simulation results of the CABRI BI1 test using the code ASTEC-Na, currently under development, as well as a comparison of the results with available experimental data. The EU-JASMIN project (7th FP of EURATOM) centres on the development and validation of the new severe accident analysis code ASTEC-Na (Accident Source Term Evaluation Code) for sodium-cooled fast reactors whose owner and developer is IRSN. A series of experiments performed in the past (CABRI/SCARABEE experiments) and new experiments to be conducted in the new experimental sodium facility KASOLA have been chosen to validate the developed ASTEC-Na code. One of the in-pile experiments considered for the validation of ASTEC-Na thermal–hydraulic models is the CABRI BI1 test, a pure loss-of-flow transient using a low burnup MOX fuel pin. The experiment resulted in a channel voiding as a result of the flow coast-down leading to clad melting. Only some fuel melting took place. Results from the analysis of this test using SIMMER and SAS-SFR codes are also presented in this work to check their suitability for further code benchmarking purposes.